Prognostic relevance of mitral and tricuspid regurgitation after transcatheter aortic valve implantation: Impact of follow-up time point for decision-making - Bäz, Laura; Möbius-Winkler, Sven; Diab, Mahmoud; Kräplin, Thomas; Westphal, Julian G.; Ibrahim, Karim; Schulze, P. Christian; Franz, Marcus (Frontiers in Cardiovascular Medicine, 2023)
Background In patients with aortic stenosis treated by transcatheter aortic valve implantation (TAVI), mitral and tricuspid regurgitation (MR and TR) at baseline and after TAVI are likely to be of prognostic relevance, and questions such as whether and when treatment further improves prognosis in these patients arise. Aims Against that background, the purpose of this study was to analyze a variety of clinical characteristics including MR and TR with respect to their potential value as predictors of 2-year mortality after TAVI. Methods A cohort of 445 typical TAVI patients was available for the study and clinical characteristics were evaluated baseline, 6 to 8 weeks as well as 6 months after TAVI. Results In 39% of the patients relevant (moderate or severe) MR and in 32% of the patients relevant (moderate or severe) TR could be detected at baseline. The rates were 27% for MR (p = 0.001, compared to baseline) and 35% for TR (p = n.s., compared to baseline) at the 6- to 8-week follow-up. After 6 months, relevant MR was observable in 28% (p = 0.036, compared to baseline) and relevant TR in 34% (p = n.s., compared to baseline) of the patients. As predictors of 2-year mortality, a multivariate analysis identified the following parameters for the different time points: sex, age, AS entity, atrial fibrillation, renal function, relevant TR, systolic pulmonary artery pressure (PAPsys), and 6-min walk distance at baseline; clinical frailty scale and PAPsys 6–8 weeks after TAVI and BNP and relevant MR 6 months after TAVI. There was a significantly worse 2-year survival in patients with relevant TR at baseline (68.4% vs. 82.6%, p < 0.001; whole population, n = 445) and in patients with relevant MR at 6 months (87.9% vs. 95.2%, p = 0.042; landmark analysis: n = 235). Conclusion This real-life study demonstrated the prognostic relevance of repeated evaluation of MR and TR before and after TAVI. Choosing the right time point for treatment is a remaining clinical challenge, which should be further addressed in randomized trials.